Eat it up! : 150 recipes to use every bit and enjoy every bite of the food you buy - Vinton, Sherri Brooks, 1968- (Da Capo Lifelong, 2016)
"Don't toss those leftovers or pitch your beet greens. Eat it up! Sherri Brooks Vinton helps you make the most of out the food you bring home. These 150 delicious recipes mine the treasure in your kitchen--the fronds from your carrots, leaves from your cauliflower, bones from Sunday's roast, even the last lick of jam in the jar are put to good, tasty use,"--page [4] of cover.